Приближенное решение одной динамической задачи геоинформатики - Булавацкий, В.М.; Скопецкий, В.В. (Проблемы управления и информатики, 2010)
Побудовано математичну модель фільтраційної консолідації деформованих насичених пористих середовищ за умов дії геохімічних процесів. Поставлено відповідну крайову задачу та запропоновано скінченноелементний алгоритм її розв’язання. The mathematical model of filtration consolidation of deformable saturated porous environments under the conditions of action of geochemical processes is constructed. The statement of corresponding boundary-value problem is given and the finite element algorithm of its solution is offered.